Maternal and Perinatal Outcome in Patients with HELLP Syndrome (Global Journal of Medical Research, 2021)
HELLP syndrome haemolysis elevated liver enzymes and low platelets is a component of hypertensive disorders of pregnancy which is associated with significant maternal as well as perinatal morbidity and mortality Maternal mortality is due to consequences such as pulmonary oedema renal failure disseminated intravascular coagulation and subcapsular liver hematoma Perinatal mortality appears to be primarily related to the gestational age at the time of delivery This study evaluates the maternal and perinatal outcome in HELLP syndrome so that the management is improved resulting in reduced mortality and morbidity Objectives A To study maternal outcome in patients diagnosed with HELLP syndrome B To study perinatal outcome in patients with HELLP syndrome
Keywords: HELLP syndrome; maternal and perinatal outcome